2012
DOI: 10.1002/smll.201201975
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Graphitic Nanocapsules for Programmed DNA Fishing and Detection

Abstract: Graphene nanomaterials are typically used in biosensing applications, and they have been demonstrated as good fluorescence quenchers. While many conventional amplification platforms are available, developing new nanomaterials and establishing simple, enzyme-free and low-cost strategies for high sensitivity biosensing is still challenging. Therefore, in this work, a core-shell magnetic graphitic nanocapsule (MGN) material is synthesized and its capabilities for the detection of biomolecules are investigated. MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…in 1 H-NMR and 3,215 cm −1 in FTIR also demonstrated the formation of an amide bond, indicating the successful synthesis of B-PEG molecules. The graphitic shell of the MGNs could quench the fluorescence of a proximal fluorophore through the fluorescence resonance energy transfer effect52. The fluorescence of the boronic acid group on B-PEG substantially decreased after interacting with the MGNs, indicating the successful functionalization of B-PEG on the surface of the MGNs (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…in 1 H-NMR and 3,215 cm −1 in FTIR also demonstrated the formation of an amide bond, indicating the successful synthesis of B-PEG molecules. The graphitic shell of the MGNs could quench the fluorescence of a proximal fluorophore through the fluorescence resonance energy transfer effect52. The fluorescence of the boronic acid group on B-PEG substantially decreased after interacting with the MGNs, indicating the successful functionalization of B-PEG on the surface of the MGNs (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Numerous studies have reported the use of magnetic CNMs for magnetic separation and purification of low-abundant biomolecules, including proteins [53e56], antigens [57], phosphopeptides [58,59], and DNA, from complex biological samples [60].…”
Section: Capture and Separation Of Cellsmentioning
confidence: 99%
“…To increase photocatalytic recyclability in waste water, we herein assembled TiO 2 nanoparticles and magnetic graphitic nanocapsules (MGN) [25][26][27] onto a graphene oxide surface to fabricate a corrosion resistant, highly effective and stable GO/magnetic graphitic nanocapsule/TiO 2 photocatalyst system (GMG-TiO 2 , Scheme 1). TiO 2 and the MGNs are synthesized through the sol-gol and chemical vapor deposition method, respectively.…”
Section: Introductionmentioning
confidence: 99%